Virgin coconut oil-based emulsion and its benefits: a review - Mohammad Latif, Muhammad Alif; Abdul Hamid, Hairul Amani; Rozani, Muhammad Afif Syazani; Mat Hadzir, Nursyamsyila (Universiti Kebangsaan Malaysia, 2024)
This review aims to provide a comprehensive overview of emulsions using virgin coconut oil (VCO) as the hydrophobic fat component. It focuses on the primary triglycerides in VCO, which convert into bioactive medium-chain triglycerides (MCTs) with diverse pharmacological properties. VCO's importance extends to aiding viral and microbial infections, leveraging its polyphenolic content as a potent antioxidant, and supporting weight reduction and metabolic improvements associated with obesity. Derived from Cocos nucifera L., VCO is a crucial plant-based oil predominantly produced in the Philippines, Malaysia, and Indonesia; regions where coconuts are in abundance. Despite VCO's extensive benefits, anti-saturated-fat bias has limited its exposure and acknowledgment in medical literature. This review addresses this gap, highlighting VCO-based emulsion applications and advantages for consumers and industries globally. By examining VCO's properties and its significant contributions to pharmaceuticals, the study aims to enhance understanding and appreciation of VCO-based emulsions. The findings underscore the need for broader recognition of VCO's potential, particularly in combating infections, acting as an antioxidant, and promoting health benefits linked to weight management and metabolic health. This review serves as a foundational reference for future research and development in utilizing VCO within pharmaceutical and health-related contexts.